Effects of fertilization in maize crops on abundance and distribution of Macrodactylus nigripes (Coleoptera: Melolonthidae) from highlands of Central Mexico - Guzmán-Mendoza, Rafael; Salas-Araiza, Manuel Darío; Calzontzi-Marín, Josefina; Martínez-Yáñez, Rosario; Pérez-Moreno, Luis (Acta Universitaria, 2016)
Macrodactylus nigripes is a pest of maize crops from central Mexico, and little is known about its ecology. The aim of this study was to analyze the abundance, distribution and density fluctuation of this species with respect to fertilization of such crop. From June to September 2008, 14 lots with different fertilization regimes were monitored with three times each month. The Analysis Of Variance (ANOVA) showed that beetle abundance was high in organic fertilization plots (PFO by its acronym in Spanish) (4.7 ± 0.54) and mixed fertilization plots (PFM by its acronym in Spanish) (4.6 ± 0.4) and low in conventional fertilization plots (PFC by its acronym in Spanish) (2.2 ± 0.2). Results also suggest that the time period has a significant effect on abundance. The patterns of distribution were different, in PFM the distribution was clumped, but in PFC there were regular and clumped distributions, and in PFO both clumped and random distributions were observed. Lots with organic fertilization promoted more beetles while more fluctuations were observed in the M. nigripes population in mixed fertilization.